PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) PILAR KETIGA PENGOLAHAN AIR MINUM BERSIH - Maria Suprianti; Fransiskus Hendro (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
The public's understanding of the cleanliness of clean drinking water management is quite good. Village socialization activities such as clean drinking water management. The total sanitation coverage in the STBM pillar in Bola Village is still relatively low. This community service aims to reconstruct the understanding of residents so that the pillars of clean drinking water management and household food are maintained. This activity is important to carry out in connection with the results of environmental observations and interviews with every resident in the field that highlights the understanding of clean drinking water management is always considered. The method used in this socialization is the lecture method in the form of counseling, storage of drinking water containers in a closed and clean place and using a healthy diet. The results of the socialization activities show that the community has understood about clean drinking water management, and each resident has made sanitation in their respective homes. The follow-up to this activity is the health party of the bola health center, and the head of the bola village should evaluate and monitor the results of the STBM trigger until the ball village really becomes a sanitation village for clean drinking water management and clean household eating.